2021
DOI: 10.3389/fphys.2021.650566
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNAs in Cardiac Regeneration

Abstract: The adult heart has a limited capacity to replace or regenerate damaged cardiac tissue following severe myocardial injury. Thus, therapies facilitating the induction of cardiac regeneration holds great promise for the treatment of end-stage heart failure, and for pathologies invoking severe cardiac dysfunction as a result of cardiomyocyte death. Recently, a number of studies have demonstrated that cardiac regeneration can be achieved through modulation and/or reprogramming of cardiomyocyte proliferation, diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 128 publications
0
24
0
Order By: Relevance
“…To fill this gap, we focused on microRNAs (miRNAs), which potently regulate multiple targets at the posttranscriptional level and modulate various steps during cardiovascular development ( 26 ). Numerous miRNAs have been described to regulate cardiomyocyte proliferation and heart repair [reviewed in ( 27 , 28 )]. Examples include miR-195 ( 29 ) and miR-99/100 ( 30 ), which have been identified to promote expression of cell cycle genes in cardiomyocytes after knockdown or promote cardiomyocyte dedifferentiation and proliferation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To fill this gap, we focused on microRNAs (miRNAs), which potently regulate multiple targets at the posttranscriptional level and modulate various steps during cardiovascular development ( 26 ). Numerous miRNAs have been described to regulate cardiomyocyte proliferation and heart repair [reviewed in ( 27 , 28 )]. Examples include miR-195 ( 29 ) and miR-99/100 ( 30 ), which have been identified to promote expression of cell cycle genes in cardiomyocytes after knockdown or promote cardiomyocyte dedifferentiation and proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, hsa - miR-590 and hsa - miR-199a , identified by screening for miRNAs promoting proliferation of neonatal cardiomyocytes ( 31 ), are not exclusively expressed in the cardiac lineage, which may suggest that cardiomyocyte-specific pathways have so far escaped identification. Likewise, several long noncoding RNAs were found to direct cardiomyocyte proliferation and cardiac regeneration, including ECRAR (endogenous cardiac regeneration-associated regulator), CRRL (cardiomyocyte regeneration-related lncRNA), and CAREL (cardiac regeneration-related lncRNA) [reviewed in ( 28 )].…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of drugs must be titrated against their off-target effects, such as negative impacts on the complement system, toxicity related to the vector, or interference with innate immunity [ 2 , 26 , 27 ]. Although some antago-miRs have been used in clinical trials against the hepatitis C virus and in other conditions [ 28 , 29 , 30 ], no study has investigated their role in cardiac tumors.…”
Section: Future Therapeutic Implicationsmentioning
confidence: 99%
“…Non-coding RNAs (ncRNAs) such as miRNAs, lncRNAs and circular RNAs (circR-NAs), play an important role in the regulation of physiologic and pathologic signaling pathways in cardiomyocytes and can be used to regulate apoptosis in CVDs and improve cardiac tissue regeneration [109]. Yan and colleagues demonstrated that in vitro overexpression of miR-31a-5p, a leading member of the miRNA-31 family, can protect against apoptosis and increase myocardial cell survival through suppression of angiotensin II-induced apoptotic pathway and caspase-3 activity by targeting Tp53 [110].…”
Section: Gene Therapy To Reduce Apoptosismentioning
confidence: 99%